Catheter ablation of atrial fibrillation with heart failure: An updated meta-analysis of randomized trials. (15th October 2018) - Kheiri, Babikir; Osman, Mohammed; Abdalla, Ahmed; Haykal, Tarek; Ahmed, Sahar; Bachuwa, Ghassan; Hassan, Mustafa; Bhatt, Deepak L.
Abstract: Introduction: Atrial fibrillation (AF) and heart failure (HF) often coexist. We conducted this meta-analysis to assess the efficacy and safety of catheter ablation in this population. Methods: Electronic databases were searched for all randomized clinical trials (RCTs) that evaluated catheter ablation in patients with left ventricular systolic dysfunction (LVSD). We calculated the weighted mean differences (MDs) and risk ratios (RRs) using a random-effects model. Results: We included 7 RCTs with 851 patients (mean follow-up was 18 months). Catheter ablation in patients with LVSD was associated with significantly lower HF hospitalization rates (RR 0.57; 95% CI: 0.45–0.72; P < 0.01), reduced all-cause mortality (RR 0.52; 95% CI: 0.35–0.76; P < 0.01), improved left ventricular ejection fraction (MD 7.40; 95% CI: 3.37–11.43; P < 0.01), increased 6-minute walk test (MD 26.96; 95% CI: 6.39–47.54; P = 0.01), and improved peak oxygen consumption (VO2 ) (MD 3.17; 95% CI: 1.05–5.28; P < 0.01), without significant increased risks of serious adverse events (RR 1.05; 95% CI: 0.96–1.16; P = 0.30) compared with medical treatment. Conclusions: In this meta-analysis of RCTs, catheter ablation was associated with significant improvements in the clinical, structural, and functional capacity of patients with AF and coexisting HF compared with medical treatment. Highlights: Catheter ablation was associated with lower heart failure hospitalization rates. Improved left ventricular ejection fraction was observed with catheter ablation. Catheter ablation was associated with improved 6-minute walk test. No increased serious adverse events were observed with catheter ablation.